The Effects of Pediatric Acute Lymphoblastic Leukemia Treatment on Cardiac Repolarization - Diana R. Lazar; Simona Cainap; Florin Leontin Lazar; Dana Maniu; Cristina Blag; Madalina Bota; Marius C. Colceriu; Mihnea Zdrenghea (MDPI AG, 2024)
Background: In recent years, cardiac dysfunction in childhood cancer survivors has become an important issue. Studies are focusing on identifying means for the early identification of patients at risk. Considering this, our study aims to investigate 24-hour Holter electrocardiogram (ECG) repolarization changes throughout doxorubicin (DOX) and cyclophosphamide (CPM) administration in pediatric patients treated for acute lymphoblastic leukemia (ALL). Methods: This was an investigator-driven, single-center, prospective, observational study. Enrolled children had a baseline bedside ECG examination performed before starting chemotherapy (T0). Serial Holter ECG examinations were conducted at three moments during their treatment protocol: day 8 (T1), day 29 (T2), and day 36 (T3). This study evaluated several ECG repolarization parameters, such as the QT interval, corrected QT interval (QTc), and QTc dispersion, as well as ST segment variations. Results: We evaluated 37 children diagnosed with ALL. The T0 examination revealed that over a third of patients had a resting heart rate (HR) outside the normal range for their age and sex. During chemotherapy, statistically significant increases in both HR as well as QT and QTc dispersion values were noticed, especially during the first DOX administration. What is more, a significant increase in the percentage of patients with ST segment depression from T1 to T2 and T3 was noticed. Rhythm disturbances were rare in the study population, with only a few patients presenting ventricular or supraventricular extrasystoles. Conclusions: This study reveals silent repolarization changes occurring early during anticancer treatment in children treated for ALL. These findings could aid in a better understanding of the cardiac toxicity mechanism, and they could potentially improve cardiac risk stratification for oncologic patients. Because of the small number of patients, our results need to be validated by larger studies.